2005
DOI: 10.1038/sj.eye.6701856
|View full text |Cite
|
Sign up to set email alerts
|

A rationale for membrane peeling in the repair of stage 4 macular holes

Abstract: Aim To examine the histological and immunocytochemical characteristics of epiretinal membranes (ERM) associated with stage 4 macular holes (MH) so as to establish a vitreoretinal rationale for surgery in stage 4 MH. Method Consecutive patients with stage 4 MH undergoing vitrectomy and membrane peeling were recruited. Preoperatively, the eyes were examined for ERM formation over the macula and completeness of posterior hyaloid membrane (PHM) separation from the retina. ERM peel specimens obtained during surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…5 In our study, 10 of 23 cases had macular TA staining, and none developed visible macular ERM, and those seven postoperative ERM cases did not had intraoperative TA staining in the corresponding area. Although PHM may be important in the formation of ERMs in other vitreoretinal diseases, such as stage 4 macular hole, 6 our study results suggest that residual hyaloid may not be a necessary factor for the development of ERMs in eyes with RD.…”
mentioning
confidence: 67%
“…5 In our study, 10 of 23 cases had macular TA staining, and none developed visible macular ERM, and those seven postoperative ERM cases did not had intraoperative TA staining in the corresponding area. Although PHM may be important in the formation of ERMs in other vitreoretinal diseases, such as stage 4 macular hole, 6 our study results suggest that residual hyaloid may not be a necessary factor for the development of ERMs in eyes with RD.…”
mentioning
confidence: 67%
“…4,5 It has also become clear that the presence or absence of a Weiss ring is insufficient for the diagnosis of complete separation of PHM. 4,5 The authors allude to the possibility of 'undetached hyaloid fragments' being related to future epiretinal membrane (ERM) formation, but recent research suggests that the evidence for PHM in this role is particularly strong. 5 Incomplete separation of the PHM, rather than the cortical gel it envelops, would explain why seven patients in the study developed ERM without any associated residual vitreous staining (with one developing severe macular pucker).…”
Section: Sir Reply To Doyle Et Almentioning
confidence: 99%
“…Based on their histopathological studies of PHM and epiretinal membrane (ERM), 3,4 the authors suggest that the ERMs developed in seven cases in our series come from undetached PHM. Ultrastructural studies of ERMs found various types of cells within the membranes, including fibrous astrocytes, fibrocytes, macrophages, and even retinal pigment epithelial cells.…”
Section: Sj Robbie and Mp Sneadmentioning
confidence: 99%
See 2 more Smart Citations